An approach to meaning and significance of the injured body in prospective physical education teachers through autobiographic narratives - Gustavo González Calvo; Lucio Martínez Álvarez (FEADEF, 2009)
This study shows how a sport injury can lead to an event that changes a prospective physical educator's life and the consequences for the personal development that result from it. The same way, the data highlight the dilemma that this person faces to feel comfortable with their own body when his «self-image» has been distorted. In doing so, the article seeks to help us to understand how individual subjectivities expressed on autobiographical narratives about sport injuries go as far as to construct and understand the body and the meaning of the self arising after the injury. With this intention in mind, we rely on the possibilities that life story provides as method of self-analysis, awareness, and a way of connecting with the embodied experiences of physical education student teachers.